Cross-linked polymer, perovskite thin film, perovskite solar cell and preparation method thereof
By using crosslinked polymers formed by trimethylolpropane tris(3-mercaptopropionate) and pentaerythritol triallyl ether in perovskite solar cells, the grain boundary and surface defects of perovskite films are passivated, The stability problem caused by small molecule instability is solved and the efficiency and stability of the battery is improved.
Patent Information
- Application Number
- CN202411236409.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-27
AI Technical Summary
The long-term stability of existing perovskite solar cells is affected by diffusion and migration problems caused by the high instability of small molecule additives, which affects the efficiency and life of the battery.
Using crosslinked polymers formed by trimethylolpropane tris(3-mercaptopropionate) and pentaerythritol triallyl ether to construct a tight hydrophobic network, passivate the grain boundary and surface defects of perovskite films, and inhibit the Intrinsic ion migration improves battery efficiency.
The open circuit voltage, filling factor and photoelectric conversion efficiency of perovskite solar cells are improved, the long-term stability of the battery is enhanced, and the high activity and fragility of small molecule monomers are solved.
Smart Images

Figure CN119192576A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solar cells, and in particular, to cross-linked polymers, perovskite films, perovskite solar cells and preparation methods thereof, and more particularly, to electrical equipment. Background Art
[0002] Among many green energy technologies, organic-inorganic halide perovskite solar cells (PSCs) have become a hot topic of research due to their excellent photoelectric performance. In recent years, in particular, the power conversion efficiency (PCE) of PSCs has exceeded 26%, which makes its commercial application prospects very broad. However, in order to realize the commercialization of PSCs, in addition to high efficiency, long-term stability is also a key factor.
[0003] Currently, small molecule additives or interface materials are widely used for passivation of perovskite thin film layers. However, the high instability of small molecules can cause them to diffuse and migrate in the perovskite thin film layer, thus affecting the long-term stability of the battery.
[0004] Therefore, it is urgent to develop new stable and effective materials to solve this problem. Summary of the invention
[0005] In the first aspect of the present application, the present application provides a cross-linked polymer. According to an embodiment of the present application, the cross-linked polymer includes at least one of the compounds represented by formula (I), 1≤n≤100;
[0006]
[0007] According to an embodiment of the present application, the cross-linked polymer is formed by a cross-linking agent trimethylolpropane tris(3-mercaptopropionate) (TMPMP) and pentaerythritol triallyl ether (PTE), and has multiple cross-linking points. Among them, pentaerythritol triallyl ether will continue to cross-link with the SH bonds in trimethylolpropane tris(3-mercaptopropionate), continuously constructing the structure shown in formula (I) to form a network structure. As a result, the cross-linked polymer has a tight hydrophobic network, which can resist the penetration of harmful molecules and effectively passivate defects at the grain boundaries and membrane surfaces (such as undercoordinated Pb 2+ ), inhibiting intrinsic ion migration, can effectively improve the efficiency of perovskite solar cells. In addition, as a macromonomer cross-linked polymer, the cross-linked polymer can solve the problem of high activity, volatility and fragile cross-linked scaffolds of small molecule monomers.
[0008] In the second aspect of the present application, the present application proposes a perovskite film. According to an embodiment of the present application, the perovskite film comprises a perovskite material and the cross-linked polymer described in the first aspect of the present application. Thus, the perovskite film can effectively passivate the grain boundaries and surface defects of the perovskite film, reduce non-radiative recombination, inhibit intrinsic ion migration, and have good passivation performance, thereby improving the open circuit voltage, fill factor, and photoelectric conversion efficiency of the perovskite solar cell.
[0009] According to an embodiment of the present application, the perovskite film may further have at least one of the following additional technical features:
[0010] In some embodiments, the mass percentage of the cross-linked polymer in the perovskite film is 0.0125% to 0.15%. Thus, the mass percentage of the cross-linked polymer in the perovskite film is moderate, which can further improve the passivation performance of the perovskite film.
[0011] In some embodiments, the mass ratio of the cross-linked polymer to the perovskite material is 1:(600-7900). Thus, the mass ratio of the cross-linked polymer to the perovskite material is moderate, which can further improve the passivation performance of the perovskite film.
[0012] In the third aspect of the present application, the present application proposes a method for preparing the aforementioned perovskite film. According to an embodiment of the present application, the method comprises: coating a perovskite precursor solution on a substrate, annealing, and forming a perovskite film; wherein the perovskite precursor solution comprises a perovskite material and a crosslinking agent, and the crosslinking agent comprises trimethylolpropane tris(3-mercaptopropionate) and pentaerythritol triallyl ether. Thus, the method can prepare a perovskite film with good passivation performance.
[0013] In some embodiments, the molar ratio of the trimethylolpropane tris(3-mercaptopropionate) to the pentaerythritol triallyl ether is 1:(0.5-2).
[0014] In some embodiments, the perovskite precursor solution further includes a hole transport material and an additive.
[0015] In some embodiments, the hole transport material comprises at least one of the compounds represented by formula (II), wherein R1 and R2 are independently selected from halogen, OH, CN, NO2, NH2, C1-C6 alkyl, C1-C6 alkoxy or C1-C6 haloalkyl;
[0016]
[0017] In some embodiments, the additive includes at least one of MACl, PbCl2, MABr, FAI and a halogen ammonium salt.
[0018] In the fourth aspect of the present application, the present application proposes a perovskite solar cell. According to an embodiment of the present application, the perovskite solar cell includes: an electrode; an electron transport layer, the electron transport layer is arranged on one side of the electrode; a perovskite film layer, the perovskite film layer includes the perovskite film described in the second aspect of the present application or the perovskite film obtained by the method described in the third aspect of the present application, and the perovskite film is arranged on the side of the electron transport layer away from the electrode; a hole transport layer, the hole transport layer is arranged on the side of the perovskite film layer away from the electron transport layer; and a transparent conductive substrate, the transparent conductive substrate is arranged on the side of the hole transport layer away from the perovskite film. As a result, the perovskite solar cell has a higher open circuit voltage, a higher fill factor and a higher photoelectric conversion efficiency.
[0019] In some embodiments, the perovskite solar cell further comprises: a passivation interface layer, wherein the passivation interface layer is disposed between the electron transport layer and the perovskite thin film layer.
[0020] In some embodiments, the thickness of the perovskite thin film layer is 200-500 nm.
[0021] In some embodiments, the thickness of the hole transport layer is 5 to 20 nm.
[0022] In some embodiments, the thickness of the passivation interface layer is 0.5-5 nm.
[0023] In some embodiments, the material of the passivation interface layer comprises at least one of the compounds represented by formula (III), wherein R3 and R4 are independently selected from Cl - Br - or I - , a is a positive integer between 1 and 20;
[0024]
[0025] In some embodiments, the material of the hole transport layer includes at least one of the compounds represented by formula (II), wherein R1 and R2 are independently selected from halogen, OH, CN, NO2, NH2, C1-C6 alkyl, C1-C6 alkoxy or C1-C6 haloalkyl;
[0026]
[0027] In the fifth aspect of the present application, the present application proposes a method for preparing the aforementioned perovskite solar cell. According to an embodiment of the present application, the method includes: forming a hole transport layer on one side of a transparent conductive substrate; forming a perovskite film layer on the side of the hole transport layer away from the transparent conductive substrate using the preparation method described in the third aspect of the present application; forming an electron transport layer on the side of the perovskite film layer away from the hole transport layer; and forming an electrode on the side of the electron transport layer away from the perovskite film layer. Thus, the method can prepare a perovskite solar cell with a higher open circuit voltage, a higher fill factor, and a higher photoelectric conversion efficiency.
[0028] In some embodiments, the method further comprises: after forming the perovskite thin film layer and before forming the electron transport layer, forming a passivation interface layer on a side of the perovskite thin film layer away from the hole transport layer.
[0029] In a sixth aspect of the present application, the present application proposes an electrical device. According to an embodiment of the present application, the electrical device includes: the perovskite solar cell described in the fifth aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0031] Figure 1 The present invention is a flow chart of a method for preparing a perovskite film in a specific embodiment of the present application.
[0032] Figure 2 A schematic diagram of the structure of a perovskite solar cell in a specific embodiment of the present application.
[0033] Figure 3 A schematic diagram of the structure of a perovskite solar cell with a passivation interface layer in a specific embodiment of the present application.
[0034] Figure 4 A flow chart of a method for preparing a perovskite solar cell in a specific embodiment of the present application.
[0035] Figure 5 A flow chart of a method for preparing a perovskite solar cell with a passivation interface layer in a specific embodiment of the present application.
[0036] Description of reference numerals:
[0037] Solar cell 101; Solar cell 102 with a passivated interface layer;
[0038] Electrode 01; electron transport layer 02; perovskite thin film layer 03; hole transport layer 04; transparent conductive substrate 05; passivation interface layer 06. DETAILED DESCRIPTION
[0039] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0040] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).
[0041] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0042] In the description of the present application, it should be understood that the terms "width", "thickness", etc. indicate orientation or positional relationships based on the orientation or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0043] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.
[0044] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.
[0045] In the description of the present application, unless otherwise clearly specified and limited, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being “above”, “above”, and “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, and “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0046] In the description of the present application, “plurality” means two or more.
[0047] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.
[0048] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0049] In the structure of organic-inorganic halide perovskite solar cells (PSCs), the upper and lower surfaces and grain boundaries of the perovskite film layer are also concentrated areas of defects, which can lead to non-radiative recombination, thus seriously affecting the efficiency of the cell. In addition, these defects are also easily corroded by external environmental factors such as water and oxygen, leading to the decomposition of the perovskite material. Therefore, the upper and lower surfaces of the perovskite film layer and the grain boundaries of the perovskite film are important factors affecting the efficiency and stability of the device.
[0050] Common small molecules are currently used as additives or interface materials for grain boundary and interface passivation. The high instability of small molecules causes a large amount of diffusion and migration in the perovskite film layer, affecting the long-term stability of the battery. In order to overcome this problem, the present application introduces a cross-linking agent trimethylolpropane tris (3-mercaptopropionate) (TMPMP) (TMPMP has a flexible main chain, which reduces the system hardness of the rigid perovskite, can well fill the grain boundaries in the perovskite body, and improve the filling of perovskite solar cells) and a cross-linked polymer shown in formula (I) formed by pentaerythritol triallyl ether (PTE) to prepare a perovskite film, effectively passivating the defects of the grain boundary and the surface of the perovskite film layer, inhibiting intrinsic ion migration, and effectively improving the efficiency of the perovskite solar cell, which is specifically manifested in improving the open circuit voltage, fill factor, and photoelectric conversion efficiency of the perovskite solar cell.
[0051] In view of this, in the first aspect of the present application, the present application proposes a cross-linked polymer. According to an embodiment of the present application, the cross-linked polymer includes at least one of the compounds represented by formula (I), 1≤n≤100;
[0052]
[0053] According to an embodiment of the present application, the cross-linked polymer is formed by a cross-linking agent trimethylolpropane tris(3-mercaptopropionate) (TMPMP) and pentaerythritol triallyl ether (PTE), and has multiple cross-linking points. Among them, pentaerythritol triallyl ether will continue to cross-link with the SH bonds in trimethylolpropane tris(3-mercaptopropionate), and continuously construct the structure shown in formula (I) ("*" is the position where the monomers in the polymer are connected to each other to form a network polymerization). As a result, the cross-linked polymer has a tight hydrophobic network, which can resist the penetration of harmful molecules and effectively passivate defects at the grain boundaries and membrane surfaces (such as undercoordinated Pb 2+ ), inhibiting intrinsic ion migration, can effectively improve the efficiency of perovskite solar cells. In addition, as a macromonomer cross-linked polymer, the cross-linked polymer can solve the problem of high activity, volatility and fragile cross-linked scaffolds of small molecule monomers.
[0054] In the second aspect of the present application, the present application proposes a perovskite film. According to an embodiment of the present application, the perovskite film comprises a perovskite material and the cross-linked polymer described in the first aspect of the present application. As a result, the perovskite film can effectively passivate the grain boundaries and surface defects of the perovskite film, reduce non-radiative recombination, inhibit intrinsic ion migration, and have good passivation performance, thereby improving the open circuit voltage, fill factor, and photoelectric conversion efficiency of the perovskite solar cell.
[0055] In some embodiments, the perovskite material is a perovskite-type ABX3 organic-inorganic hybrid material. Wherein A includes but is not limited to methylamine cation (FA + ), methylammonium cation (MA + ), cesium cation (Cs + ), rubidium cation (Rb + ), potassium cation (K + ) at least one of; B includes but is not limited to lead cations (Pb 2+ ), tin cation (Sn 2+ ), copper cation (Cu 2+ ), zinc cation (Zn 2+ ), gallium cation (Ga 2+ ), calcium cation (Ca 2+ ) at least one of; X includes but is not limited to fluoride anion (F - ), chloride anion (Cl - ), bromide anion (Br- ), iodide anion (I - )
[0056] In some embodiments, the cross-linked polymer accounts for 0.0125% to 0.15% by mass of the perovskite film, for example, 0.0125%, 0.0126%, 0.0127%, 0.0128%, 0.0129%, 0.013%, 0.0131%, 0.0132%, 0.0133%, 0.0134%, 0.0135%, 0.0136%, 0.0137%, 0.0138%, 0.0139%, 0.014%, 0.0145%, 0.015% or a range of 0.0126% to 0.15%, 0.0127% to 0.15%, 0.0128% to 0.15%, 0.0128% to 0.0145%, 0.0128% to 0.014%, 0.0128% to 0.0135%, 0.0128% to 0.0133%, 0.0128% to 0.0131% or 0.0129% to 0.0131%. Thus, the cross-linked polymer accounts for a moderate mass percentage of the perovskite film, which can further improve the passivation performance of the perovskite film.
[0057] In some embodiments, the mass percentage of the cross-linked polymer in the perovskite film is 0.0129% to 0.0131%. Thus, the mass percentage of the cross-linked polymer in the perovskite film is moderate, which can further improve the passivation performance of the perovskite film.
[0058] In some embodiments, the mass percentage of the cross-linked polymer in the perovskite film is 0.013%. Thus, the mass percentage of the cross-linked polymer in the perovskite film is moderate, which can further improve the passivation performance of the perovskite film.
[0059] In some embodiments, the mass ratio of the cross-linked polymer to the perovskite material is 1:(600-7900). Thus, the mass ratio of the cross-linked polymer to the perovskite material is moderate, which can further improve the passivation performance of the perovskite film.
[0060] In some embodiments, the mass ratio of the cross-linked polymer to the perovskite material is 1:(768-770). Thus, the mass ratio of the cross-linked polymer to the perovskite material is moderate, which can further improve the passivation performance of the perovskite film.
[0061] In some embodiments, the mass ratio of the cross-linked polymer to the perovskite material is 1: 769. Thus, the mass ratio of the cross-linked polymer to the perovskite material is moderate, which can further improve the passivation performance of the perovskite film.
[0062] In the third aspect of the present application, the present application proposes a method for preparing the aforementioned perovskite film, comprising: coating a perovskite precursor solution on a substrate, annealing, and forming a perovskite film; wherein the perovskite precursor solution comprises a perovskite material and a crosslinking agent, and the crosslinking agent comprises trimethylolpropane tris(3-mercaptopropionate) and pentaerythritol triallyl ether. Thus, the method can prepare a perovskite film with good passivation performance.
[0063] In some embodiments, the molar ratio of the trimethylolpropane tris(3-mercaptopropionate) to the pentaerythritol triallyl ether is 1:(0.5-2), for example, it can be 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2 or a range value therebetween 1:(0.5-1.9), 1:(0.5-1.8) or 1:(0.5-1.7). The molar ratio of the trimethylolpropane tris(3-mercaptopropionate) to the pentaerythritol triallyl ether is moderate, which is conducive to the full reaction of trimethylolpropane tris(3-mercaptopropionate) and pentaerythritol triallyl ether to form a cross-linked poly(trimethylolpropane tris(3-mercaptopropionate))-pentaerythritol triallyl ether.
[0064] In some embodiments, the concentration of trimethylolpropane tris(3-mercaptopropionate) in the perovskite precursor solution is 0.1 mg / mL-2 mg / mL.
[0065] In some embodiments, the concentration of the pentaerythritol triallyl ether in the perovskite precursor solution is 0.1 mg / mL-2 mg / mL.
[0066] In some embodiments, the concentration of the perovskite material in the perovskite precursor solution is 0.1 mg / mL-2 mg / mL.
[0067] In some embodiments, the perovskite precursor solution further includes a hole transport material and an additive. According to an embodiment of the present application, a one-step method is used to prepare the perovskite precursor solution, and a hole transport material (self-assembled monomolecular material) is added to form a hole transport layer by anchoring. In addition, adding additives can promote the crystallization process of the perovskite film, improve the quality of the perovskite film, thereby improving the performance of the perovskite solar cell, and adding additives helps to passivate defects in the perovskite film, reduce non-radiative recombination, and improve the photoelectric conversion efficiency of the perovskite solar cell.
[0068] In some embodiments, the hole transport material comprises at least one of the compounds represented by formula (II), wherein R1 and R2 are independently selected from halogen, OH, CN, NO2, NH2, C1-C6 alkyl, C1-C6 alkoxy or C1-C6 haloalkyl;
[0069]
[0070] For example, the hole transport material in the embodiment of the present application is (4-(2,7-dibromo-9,9-dimethylacridin-10(9H)-yl)butyl)phosphonic acid.
[0071] In some embodiments, the concentration of the hole transport material in the perovskite precursor solution is 0.5 mg / mL-3 mg / mL.
[0072] In some embodiments, the additive includes at least one of MACl, PbCl2, MABr, FAI and halogen ammonium salts. According to embodiments of the present application, additives such as MACl (formamidinium chloride) can promote the crystallization process of the perovskite film, improve the quality of the perovskite film, thereby improving the performance of the perovskite solar cell, and help passivate the defects in the perovskite film, reduce non-radiative recombination, and improve the photoelectric conversion efficiency of the perovskite solar cell.
[0073] In some embodiments, the perovskite precursor solution further includes a solvent.
[0074] In some embodiments, the solvent includes at least one of N,N dimethylformamide, N-methylpyrrolidone, acetonitrile, dimethyl sulfoxide, ethanol and acetone. According to an embodiment of the present application, the solvent of the present application is N,N dimethylformamide and N-methylpyrrolidone, which are used to dissolve perovskite precursor materials (such as FAI, PbI2, CsI) and additives (such as MACl), hole transport materials and cross-linking agents (such as TMPMP and PTE) to form a uniform perovskite precursor solution, improve the crystallinity of the perovskite film, defect density and the photoelectric performance of the final perovskite solar cell.
[0075] In some embodiments, reference Figure 1 , the method for preparing the aforementioned perovskite film comprises:
[0076] S100, mixing the perovskite material, the cross-linking agent, the additive, the hole transport material, and the solvent to form a perovskite precursor solution. Among them, doping the cross-linking agent in the perovskite material can play the effect of synchronous annealing and in-situ thermal cross-linking with the perovskite material, inhibiting the thermal expansion of the perovskite material during the annealing process and releasing the residual strain; in the post-film processing of the perovskite material, a dense layer of cross-linked polymer is formed to effectively encapsulate it.
[0077] S200, the perovskite precursor solution obtained in S100 is applied to the surface of the ITO substrate by spin coating in one step, and a perovskite film layer and a hole transport layer are formed simultaneously. The hole transport material in the perovskite precursor solution will cross-link with the TCO substrate to form a hole transport layer, which is distinguished from the perovskite film layer.
[0078] S300, annealing the substrate coated in S200. During the annealing process in step S300, trimethylolpropane tris(3-mercaptopropionate) and pentaerythritol triallyl ether are cross-linked to form a cross-linked polymer represented by formula (I), i.e., cross-linked poly(trimethylolpropane tris(3-mercaptopropionate))-pentaerythritol triallyl ether, the cross-linked polymer is mainly distributed on the top of the perovskite film layer, and a small part is distributed at the junction of the perovskite film layer and the hole transport layer, forming a network lattice structure, effectively passivating grain boundaries and film surface defects, inhibiting intrinsic ion migration, and effectively improving the efficiency of the perovskite solar cell.
[0079] In a fourth aspect of the present application, the present application proposes a perovskite solar cell. According to an embodiment of the present application, referring to Figure 2 The perovskite solar cell 101 includes: an electrode 01; an electron transport layer 02, the electron transport layer 02 is arranged on one side of the electrode 01; a perovskite film layer 03, the perovskite film layer 03 includes the perovskite film described in the second aspect of the present application or the perovskite film prepared by the method described in the third aspect of the present application, the perovskite film layer 03 is arranged on the side of the electron transport layer 02 away from the electrode 01; a hole transport layer 04, the hole transport layer 04 is arranged on the side of the perovskite film layer 03 away from the electron transport layer 02; and a transparent conductive substrate 05, the transparent conductive substrate 05 is arranged on the side of the hole transport layer 04 away from the perovskite film 03.
[0080] According to an embodiment of the present application, the perovskite thin film layer in the perovskite solar cell described in the present application includes the aforementioned perovskite thin film, which is composed of the aforementioned cross-linked polymer. The cross-linked polymer has a compact hydrophobic network, which can resist the penetration of harmful molecules and effectively passivate defects at the grain boundaries and film surfaces (such as under-coordinated Pb 2+ ), inhibiting intrinsic ion migration, thereby effectively improving the efficiency of the perovskite solar cell. As a result, the perovskite solar cell with the aforementioned cross-linked polymer in the embodiment of the present application has a higher open circuit voltage, a higher fill factor and a higher photoelectric conversion efficiency.
[0081] In some embodiments, the method for preparing a hole transport layer and a perovskite film layer in the present application can be formed by coating a mixture of a perovskite precursor solution and a hole transport material on a substrate by a one-step method, annealing, and simultaneously forming a hole transport layer and a perovskite film layer. Wherein, the perovskite precursor solution includes a perovskite material and a cross-linking agent, and the cross-linking agent includes trimethylolpropane tris (3-mercaptopropionate) and pentaerythritol triallyl ether; the hole transport material will cross-link and anchor with the TCO substrate in the perovskite solar cell to form a hole transport layer, thereby distinguishing it from the perovskite film layer formed by the perovskite precursor solution.
[0082] In some embodiments, the method for preparing the perovskite film layer and the hole transport layer in the present application can first coat the hole transport material on the substrate to form the hole transport layer. Then, the perovskite precursor solution is coated on the substrate and annealed to form the perovskite film layer. The hole transport layer and the perovskite film layer are formed by a two-step coating method. The perovskite precursor solution includes a perovskite material and a cross-linking agent, and the cross-linking agent includes trimethylolpropane tris (3-mercaptopropionate) and pentaerythritol triallyl ether.
[0083] According to an embodiment of the present application, it is preferred that a mixture of a perovskite precursor solution and a hole transport material is coated on a substrate by a one-step method, annealed, and a hole transport layer and a perovskite film layer are formed simultaneously. The one-step method is adopted to prepare, and a self-assembled monolayer material is introduced into the perovskite precursor solution, and a hole transport layer is formed by anchoring. Thus, the aforementioned cross-linked polymer can simultaneously passivate the interface between the hole transport layer and the perovskite film layer and the interface on the perovskite film layer, simplifying the preparation process.
[0084] In some embodiments, reference Figure 3 The perovskite solar cell 102 further includes: a passivation interface layer 06 , and the passivation interface layer 06 is arranged between the electron transport layer 02 and the perovskite thin film layer 03 .
[0085] In some embodiments, the thickness of the perovskite film layer is 200-500 nm, for example, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 460 nm, 470 nm, 480 nm, 490 nm, 500 nm and the range values 210-500 nm, 220-500 nm and 230-500 nm therebetween. Thus, the thickness of the perovskite film layer is moderate, which can further improve the open circuit voltage, fill factor and photoelectric conversion efficiency of the perovskite solar cell.
[0086] In some embodiments, the thickness of the hole transport layer is 5 to 20 nm, for example, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm and the ranges between 6 to 20 nm, 7 to 20 nm and 8 to 20 nm. Thus, the thickness of the hole transport layer is moderate, which can further improve the open circuit voltage, fill factor and photoelectric conversion efficiency of the perovskite solar cell.
[0087] In some embodiments, the thickness of the passivation interface layer is 0.5 to 5 nm, for example, 0.5 nm, 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm, 1 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm, 1.5 nm, 1.6 nm, 1.7 nm, 1.8 nm, 1.9 nm, 2 nm, 2.1 nm, 2.2 nm, 2.3 nm, 2.4 nm, 2.5 nm, 2.6 nm, 2.7 nm , 2.8nm, 2.9nm, 3nm, 3.1nm, 3.2nm, 3.3nm, 3.4nm, 3.5nm, 3.6nm, 3.7nm, 3.8nm, 3.9nm, 4nm, 4.1nm, 4.2nm, 4.3nm, 4.4nm, 4.5nm, 4.6nm, 4.7nm, 4.8nm, 4.9nm, 5nm and ranges between 0.6-5nm, 0.7-5nm and 0.8-5nm. Thus, the thickness of the passivation interface layer is moderate, which can further improve the open circuit voltage, fill factor and photoelectric conversion efficiency of the perovskite solar cell.
[0088] In some embodiments, the material of the passivation interface layer comprises at least one of the compounds represented by formula (III), wherein R3 and R4 are independently selected from Cl - Br - or I - , a is a positive integer between 1 and 20;
[0089]
[0090] In some embodiments, the material of the hole transport layer includes at least one of the compounds represented by formula (II), wherein R1 and R2 are independently selected from halogen, OH, CN, NO2, NH2, C1-C6 alkyl, C1-C6 alkoxy or C1-C6 haloalkyl;
[0091]
[0092] In some embodiments, the perovskite solar cell includes at least one of a single-junction perovskite solar cell, a two-terminal tandem perovskite solar cell, and a four-terminal tandem solar cell.
[0093] In a fifth aspect of the present application, the present application proposes a method for preparing the aforementioned perovskite solar cell. According to an embodiment of the present application, referring to Figure 4 , the method comprising:
[0094] S1000: forming a hole transport layer on one side of the transparent conductive substrate;
[0095] S2000: forming a perovskite thin film layer on a side of the hole transport layer away from the transparent conductive substrate using the preparation method described in the third aspect of the present application;
[0096] S3000: forming an electron transport layer on a side of the perovskite thin film layer away from the hole transport layer;
[0097] S4000: Forming an electrode on a side of the electron transport layer away from the perovskite thin film layer.
[0098] Thus, the method can prepare a perovskite solar cell with a higher open circuit voltage, a higher fill factor and a higher photoelectric conversion efficiency. The perovskite solar cell prepared according to the method of the embodiment of the present application includes the aforementioned perovskite film, and the aforementioned perovskite film includes the aforementioned cross-linked polymer. Among them, the cross-linked polymer has a tight hydrophobic network, which can resist the penetration of harmful molecules and effectively passivate defects at the grain boundaries and the film surface (such as undercoordinated Pb 2+ ), inhibiting intrinsic ion migration, thereby effectively improving the efficiency of the perovskite solar cell. As a result, the perovskite solar cell prepared by the method of the embodiment of the present application has a higher open circuit voltage, a higher fill factor and a higher photoelectric conversion efficiency.
[0099] In some embodiments, reference Figure 5 , the method comprising:
[0100] S1000: forming a hole transport layer on one side of the transparent conductive substrate;
[0101] S2000: forming a perovskite thin film layer on a side of the hole transport layer away from the transparent conductive substrate using the preparation method described in the third aspect of the present application;
[0102] S3000: forming a passivation interface layer on a side of the perovskite thin film layer away from the hole transport layer;
[0103] S4000: forming an electron transport layer on a side of the passivation interface layer away from the perovskite thin film layer;
[0104] S5000: Forming an electrode on a side of the electron transport layer away from the passivation interface layer.
[0105] In the sixth aspect of the present application, the present application proposes an electrical device, including: the perovskite solar cell or perovskite tandem cell described in the fifth aspect.
[0106] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.
[0107] Example 1
[0108] The perovskite solar cell preparation process of this application is as follows:
[0109] (1) The indium-based tin oxide conductive glass was ultrasonically cleaned with glass cleaning liquid, deionized water, and ethanol for 20 minutes respectively, and finally placed in a drying oven at 75° C. for use; the dried indium-based tin oxide conductive glass substrate was placed in an ultraviolet ozone machine for 20 minutes to remove organic impurities on its surface and optimize its surface wettability;
[0110] (2) Appropriate amounts of FAI, PbI2, and CsI were weighed to form a perovskite precursor with a solution concentration of 1.5 M, 10 wt% MACl was added as an additive, and 1.5 mg of (4-(2,7-dibromo-9,9-dimethylacridine-10(9H)-yl)butyl)phosphonic acid was added as a hole transport material, 0.41 μL of TMPMP and 0.73 mg of PTE were added as a cross-linking agent, the molar ratio of TMPMP to PTE was 1:1, and the concentration of the formed cross-linked polymer was 0.5 mg / mL), dissolved in a mixed solvent of DMF / NMP (5:1, v / v), and the solvent totaled 1.2 mL to obtain FA. 0.85 MA 0.05 Cs 0.1 Perovskite precursor solution of PbI3. XPS test shows that the mass fraction of the cross-linked polymer formed by TMPMP and PTE in the perovskite film layer is 0.0552%.
[0111] (3) In a nitrogen glove box, 60 μL of the perovskite precursor solution was spin-coated on the surface of an indium-based tin oxide conductive glass substrate at a speed of 5000 rpm / min and an acceleration of 1000 rpm / s for 50 s. After completion, the substrate was transferred to an annealing hot plate and heated at 100 °C for 40 min to complete annealing.
[0112] (4) Propylenediamine hydroiodide was dissolved in an IPA solution at a concentration of 0.8 mg / mL and coated on the perovskite surface by spin coating at a speed of 5000 rpm / min and an acceleration of 3000 rpm / s for 30 s, and annealed on a hot stage at 100°C for 15 min to form a passivation interface layer.
[0113] (5) 20 nm of C60, 15 nm of BCP and 150 nm of Ag were sequentially deposited on the above substrates as the electron transport layer and the top electrode, respectively.
[0114] Example 2
[0115] The experimental process of Example 2 is basically the same as that of Example 1, except that 1.24 μL of TMPMP and 2.18 mg of PTE are added as crosslinking agents, and the concentration of the crosslinked polymer formed by TMPMP and PTE is 1.5 mg / mL (the molar ratio of TMPMP to PTE is 1:1). XPS testing shows that the mass fraction of the crosslinked polymer in the perovskite film layer is 0.1473%.
[0116] Example 3
[0117] The experimental process of Example 3 is basically the same as that of Example 1, except that 0.08 μL of TMPMP and 0.15 mg of PTE are added as crosslinking agents, and the concentration of the crosslinked polymer formed by TMPMP and PTE is 0.1 mg / mL (the molar ratio of TMPMP to PTE is 1:1). XPS testing shows that the mass fraction of the crosslinked polymer in the perovskite film layer is 0.0125%.
[0118] Example 4
[0119] The experimental process of Example 4 is basically the same as that of Example 1, except that 1.65 μL of TMPMP and 2.9 mg of PTE are added as crosslinking agents, and the concentration of the crosslinked polymer formed by TMPMP and PTE is 2 mg / mL (the molar ratio of TMPMP to PTE is 1:1). XPS test shows that the mass fraction of the crosslinked polymer in the perovskite film layer is 0.2381%.
[0120] Example 5
[0121] The experimental process of Example 5 is basically the same as that of Example 1, except that the molar ratio of the added TMPMP to PTE is 1:0.5. XPS test shows that the mass fraction of the cross-linked polymer in the perovskite film layer is 0.0331%.
[0122] Example 6
[0123] The experimental process of Example 6 is basically the same as that of Example 1, except that the molar ratio of the added TMPMP to PTE is 1:0.75. XPS test shows that the mass fraction of the cross-linked polymer in the perovskite film layer is 0.0517%.
[0124] Example 7
[0125] The experimental process of Example 7 is basically the same as that of Example 1, except that the molar ratio of the added TMPMP to PTE is 1:1.5. XPS test shows that the mass fraction of the cross-linked polymer in the perovskite film layer is 0.0677%.
[0126] Example 8
[0127] The experimental process of Example 8 is basically the same as that of Example 1, except that the perovskite solar cell prepared in Example 7 does not form a passivation interface layer.
[0128] Example 9
[0129] The experimental process of Example 9 is basically the same as that of Example 1, except that the perovskite solar cell prepared in Example 8 does not form a passivation interface layer.
[0130] Comparative Example 1
[0131] The experimental process of Comparative Example 1 is basically the same as that of Example 1, except that TMPMP and PTE are not added.
[0132] Comparative Example 2
[0133] The experimental process of Comparative Example 2 is basically the same as that of Example 1, except that TMPMP is replaced with trimethylolpropane triacrylate, 0.46 μL of trimethylolpropane triacrylate and 0.73 mg of pentaerythritol triallyl ether are used as crosslinking agents (the molar ratio of trimethylolpropane triacrylate to pentaerythritol triallyl ether is 1:1, and the concentration of the formed crosslinked polymer is 0.5 mg / mL). XPS test shows that the mass fraction of the crosslinked polymer in the perovskite film layer is 0.0448%.
[0134] Comparative Example 3
[0135] The experimental process of Comparative Example 3 is basically the same as that of Example 1, except that PTE is replaced with pentaerythritol tetraallyl ether, 0.41 μL of trimethylolpropane tris(3-mercaptopropionate) and 0.84 mg of pentaerythritol tetraallyl ether are used as crosslinking agents (the molar ratio of trimethylolpropane tris(3-mercaptopropionate) to pentaerythritol tetraallyl ether is 1:1, and the concentration of the formed crosslinked polymer is 0.5 mg / mL). XPS test shows that the mass fraction of the crosslinked polymer in the perovskite film layer is 0.0597%.
[0136] In accordance with the IEC 61730 standard, the open circuit voltage Voc, short circuit current density Jsc, fill factor FF, and photoelectric conversion efficiency PCE of the solar cells prepared in Examples 1-9 and Comparative Examples 1-3 were tested. The test results are shown in Table 1.
[0137] Table 1
[0138]
[0139]
[0140] At a light intensity of 100 mW cm -2 Under the irradiation conditions of simulated sunlight AM1.5G, the concentration of the cross-linked polymer in Example 1 is 0.5 mg / mL (the mass fraction of the cross-linked polymer in the perovskite film is 0.0552%) and the Voc, FF and PCE are the highest when the passivation interface layer is added, and the Voc can reach 1.14 V, the FF can reach 84.34%, and the PCE can reach 23.47%.
[0141] By comparing Example 1 with Examples 2-4, it can be seen that when the concentration of the cross-linked polymer is 0.1 mg / mL-1.5 mg / mL, that is, when the mass fraction of the cross-linked polymer in the perovskite film layer is 0.0125% to 0.15%, it is beneficial to improve the open circuit voltage, fill factor and photoelectric conversion efficiency of the perovskite solar cell.
[0142] By comparing Example 1 with Examples 5-7, it can be seen that a moderate molar ratio of TMPMP to PTE can improve the open circuit voltage, fill factor and photoelectric conversion efficiency of the perovskite solar cell.
[0143] By comparing Example 1 and Example 8, it can be seen that the open circuit voltage, fill factor and photoelectric conversion efficiency of the perovskite solar cell prepared in Example 1 are improved when a passivation interface layer is formed, and the open circuit voltage, fill factor and photoelectric conversion efficiency of the perovskite solar cell prepared in Example 8 are reduced when a passivation interface layer is not formed, indicating that the formation of a passivation interface layer in the perovskite solar cell is beneficial to further improve the open circuit voltage, fill factor and photoelectric conversion efficiency of the perovskite solar cell.
[0144] By comparing Example 1 and Example 9, it can be seen that the open circuit voltage and photoelectric conversion efficiency of the perovskite solar cell prepared in Example 1 are improved when a passivation interface layer is formed. When the perovskite solar cell prepared in Example 9 does not form a passivation interface layer, although the filling factor is slightly improved, its open circuit voltage and photoelectric conversion efficiency decrease, indicating that the formation of a passivation interface layer in the perovskite solar cell is beneficial to further improve the open circuit voltage and photoelectric conversion efficiency of the perovskite solar cell.
[0145] By comparing Example 1 with Comparative Example 1, it can be seen that the open circuit voltage, fill factor, and photoelectric conversion efficiency of the perovskite solar cell prepared by adding the cross-linked polymer prepared by TMPMP and PTE cross-linking agents are significantly improved, and the open circuit voltage, fill factor, and photoelectric conversion efficiency of the perovskite solar cell prepared without adding TMPMP and PTE cross-linking agents are significantly reduced, indicating that the formation of the cross-linked polymer represented by formula (I) is beneficial to improving the open circuit voltage, fill factor, and photoelectric conversion efficiency of the perovskite solar cell.
[0146] By comparing Example 1 and Comparative Example 2, it can be seen that the open circuit voltage, fill factor and photoelectric conversion efficiency of the perovskite solar cell prepared by adding the cross-linked polymer prepared by TMPMP and PTE cross-linking agents are significantly improved. When TMPMP is replaced with trimethylolpropane triacrylate, the open circuit voltage, fill factor and photoelectric conversion efficiency of the prepared perovskite solar cell are significantly reduced, indicating that the cross-linked polymer represented by formula (I) formed by adding TMPMP and PTE cross-linking agents is beneficial to improving the open circuit voltage, fill factor and photoelectric conversion efficiency of the perovskite solar cell.
[0147] By comparing Example 1 and Comparative Example 3, it can be seen that the open circuit voltage, filling factor and photoelectric conversion efficiency of the perovskite solar cell prepared by adding the cross-linked polymer prepared by TMPMP and PTE cross-linking agents are significantly improved. When PTE is replaced with pentaerythritol tetraallyl ether, the open circuit voltage, filling factor and photoelectric conversion efficiency of the prepared perovskite solar cell are significantly reduced, indicating that the cross-linked polymer represented by formula (I) formed by adding TMPMP and PTE cross-linking agents is beneficial to improving the open circuit voltage, filling factor and photoelectric conversion efficiency of the perovskite solar cell.
[0148] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0149] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A cross-linked polymer, characterized in that Including at least one of the compounds represented by formula (I), 1≤n≤100; 2. A perovskite film, characterized in that: The perovskite film comprises a perovskite material and the cross-linked polymer according to claim 1.
3. The perovskite film according to claim 2, characterized in that: The mass percentage of the cross-linked polymer in the perovskite film is 0.0125% to 0.15%.
4. The perovskite film according to claim 2, characterized in that: The mass ratio of the cross-linked polymer to the perovskite material is 1:(600-7900).
5. A method for preparing the perovskite film according to any one of claims 2 to 4, characterized in that: include: coating a perovskite precursor solution on a substrate and annealing to form a perovskite film; The perovskite precursor solution includes a perovskite material and a cross-linking agent, and the cross-linking agent includes trimethylolpropane tris(3-mercaptopropionate) and pentaerythritol triallyl ether.
6. The method according to claim 5, characterized in that The molar ratio of the trimethylolpropane tris(3-mercaptopropionate) to the pentaerythritol triallyl ether is 1:(0.5-2).
7. The method according to claim 6, characterized in that The perovskite precursor solution further includes a hole transport material and an additive.
8. The method according to claim 7, characterized in that The hole transport material comprises at least one of the compounds represented by formula (II), wherein R1 and R2 are independently selected from halogen, OH, CN, NO2, NH2, C1-C6 alkyl, C1-C6 alkoxy or C1-C6 haloalkyl; 9. The method according to claim 7, characterized in that: The additive includes at least one of MACl, PbCl2, MABr, FAI and halogen ammonium salt.
10. A perovskite solar cell, characterized in that: include: electrode; An electron transport layer, the electron transport layer is arranged on one side of the electrode; A perovskite film layer, wherein the perovskite film layer comprises the perovskite film according to any one of claims 2 to 4 or a perovskite film prepared by the method according to any one of claims 5 to 9, and the perovskite film is disposed on a side of the electron transport layer away from the electrode; A hole transport layer, the hole transport layer being disposed on a side of the perovskite thin film layer away from the electron transport layer; and A transparent conductive substrate is disposed on a side of the hole transport layer away from the perovskite film.
11. The perovskite solar cell according to claim 10, characterized in that: Further including: A passivation interface layer is disposed between the electron transport layer and the perovskite thin film layer.
12. The perovskite solar cell according to claim 11, characterized in that: The thickness of the perovskite thin film layer is 200-500 nm; and / or the thickness of the hole transport layer is 5-20 nm; and / or the thickness of the passivation interface layer is 0.5-5 nm.
13. The perovskite solar cell according to claim 12, characterized in that: The material of the passivation interface layer includes at least one of the compounds represented by formula (III), wherein R3 and R4 are independently selected from Cl - Br - or I - , a is a positive integer between 1 and 20; 14. The perovskite solar cell according to claim 12, characterized in that: The material of the hole transport layer includes at least one of the compounds represented by formula (II), wherein R1 and R2 are independently selected from halogen, OH, CN, NO2, NH2, C1-C6 alkyl, C1-C6 alkoxy or C1-C6 haloalkyl; 15. A method for preparing the perovskite solar cell according to claims 10 to 14, characterized in that: include: forming a hole transport layer on one side of the transparent conductive substrate; Forming a perovskite thin film layer on a side of the hole transport layer away from the transparent conductive substrate using the preparation method described in any one of claims 5 to 9; forming an electron transport layer on a side of the perovskite thin film layer away from the hole transport layer; An electrode is formed on a side of the electron transport layer away from the perovskite thin film layer.
16. The method according to claim 15, characterized in that Further including: After forming the perovskite thin film layer and before forming the electron transport layer, a passivation interface layer is formed on a side of the perovskite thin film layer away from the hole transport layer.
17. An electrical equipment, characterized in that: include: The perovskite solar cell according to any one of claims 10 to 14 or the perovskite solar cell prepared by the method according to any one of claims 15 or 16.
Citation Information
Cited By
Polymer additive as well as preparation method and application thereof
CN119798652A